Do females preferentially associate with males given a better start in life? - Kahn, Andrew T. (The Royal Society, 2012)
A poor start in life owing to a restricted diet can have readily detectable detrimental consequences for many adult life-history traits. However, some costs such as smaller adult body size are potentially eliminated when individuals modify their development. For example, male mosquitofish (Gambusia holbrooki) that have reduced early food intake undergo compensatory growth and delay maturation so that they eventually mature at the same size as males that develop normally. But do subtle effects of a poor start persist? Specifically, does a male's developmental history affect his subsequent attractiveness to females? Females prefer to associate with larger males but, controlling for body length, we show that females spent less time in association with males that underwent compensatory growth than with males that developed normally.